Randomized Trial of Vitamin D Supplementation to Prevent Seasonal Influenza and Upper Respiratory Infection in Patients With Inflammatory Bowel Disease. Issue 6 (2nd January 2019) - Arihiro, Seiji; Nakashima, Akio; Matsuoka, Mika; Suto, Satoshi; Uchiyama, Kan; Kato, Tomohiro; Mitobe, Jimi; Komoike, Nobuhiko; Itagaki, Munenori; Miyakawa, Yoshinari; Koido, Shigeo; Hokari, Atsushi; et al.
Abstract: Background: We evaluated whether oral vitamin D supplementation during the winter and early spring reduces the incidence of influenza and upper respiratory infections in patients with inflammatory bowel disease (IBD). Methods: A randomized, double-blind, controlled trial was conducted to compare the effects of vitamin D supplementation (500 IU/day) and a placebo. The primary outcome was the incidence of influenza; the secondary outcome was the incidence of upper respiratory infection. Prespecified subgroup analyses were performed according to 25-hydroxyvitamin D (25-OHD) levels (low <20 ng/mL or high ≥20 ng/mL) and whether ulcerative colitis (UC) or Crohn's disease (CD) was present. We also used the Lichtiger clinical activity index for patients with UC and the Crohn's Disease Activity Index (CDAI) for patients with CD before and after interventions. Results: We included 223 patients with IBD and randomized them into 2 groups: vitamin D supplementation (n = 108) and placebo (n = 115). The incidence of influenza did not differ between the groups. However, the incidence of upper respiratory infection was significantly lower in the vitamin D group (relative risk [RR], 0.59; 95% confidence interval (CI), 0.35–0.98; P = 0.042). This effect was enhanced in the low 25-OHD level subgroup (RR, 0.36; 95% CI, 0.14–0.90; P = 0.02). With respect to adverse events, the Lichtiger clinical activity index score was significantly worse in the vitamin D group ( P = 0.002) and remained significant only in the high 25-OHD level subgroup. Conclusions: Vitamin D supplementation may have a preventative effect against upper respiratory infection in patients with IBD but may worsen the symptoms of UC.